2011
DOI: 10.1517/17425255.2012.639360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of posaconazole on the pharmacokinetics of simvastatin and midazolam in healthy volunteers

Abstract: These findings support the classification of posaconazole as a strong CYP3A4 inhibitor. Simvastatin, or other statins predominantly metabolized by CYP3A4, should not be co-administered with posaconazole. Other statins, whose metabolism/elimination is not affected by CYP3A4 inhibition, should be considered for co-administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
4
25
0
1
Order By: Relevance
“…The antifungal azole derivatives intraconazole, ketoconazole and posaconazole are very potent and effective inhibitors of CYP3A4 4. All have been shown to cause an at least fivefold increase in the plasma concentration of simvastatin in drug–drug interaction studies performed in healthy volunteers,3 5 6 and rhabdomyolysis in the context of concomitant use of simvastatin and itraconazole has been described in case reports similar to the present one 7–10. The present case contributes by further confirming the clinical relevance of the drug–drug interaction in younger patients, as the prior reported cases have been in elderly patients with several comorbidities and comedications 7–10…”
Section: Discussionsupporting
confidence: 70%
“…The antifungal azole derivatives intraconazole, ketoconazole and posaconazole are very potent and effective inhibitors of CYP3A4 4. All have been shown to cause an at least fivefold increase in the plasma concentration of simvastatin in drug–drug interaction studies performed in healthy volunteers,3 5 6 and rhabdomyolysis in the context of concomitant use of simvastatin and itraconazole has been described in case reports similar to the present one 7–10. The present case contributes by further confirming the clinical relevance of the drug–drug interaction in younger patients, as the prior reported cases have been in elderly patients with several comorbidities and comedications 7–10…”
Section: Discussionsupporting
confidence: 70%
“…For rifampin, a systematic search identified three PK studies [26][27][28] assessing the impact of single dose and four PK studies [29][30][31][32] assessing the impact of multiple doses. Eight [33][34][35][36][37][38][39][40] PK studies were identified for azole antifungals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Posaconazole is a strong CYP3A4 inhibitor and increases the AUC of simvastatin acid by approximately 7-8 times its original value [40]. Per prescribing information, its administration is contraindicated with simvastatin, lovastatin, and atorvastatin [58].…”
Section: Statins Interactions With Azole Antifungalsmentioning
confidence: 99%
“…However, simvastatin is a substrate of cytochrome P450 3A4 and as a consequence coadministration with potent inhibitors of cytochrome P450 3A4 increases the concentration of HMG-CoA reductase inhibitory activity in plasma and the risk of myopathy and rhabdomyolysis. Hence, the coadministration of simvastatin with ketoconazole, itraconazole, posaconazole, clarithromycin, telithromycin, erythromycin, HIV protease inhibitors (e.g., nelfinavir), danazol and nefazodone is contraindicated [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157]. If the administration of a CYP3A4 inhibitor is needed then simvastatin treatment should be at least temporarily stopped.…”
Section: Brief Description Of Drug Interactionsmentioning
confidence: 99%